Clinico-functional assessment of patients with pachychoroid neovasculopathy after intravitreal administration of angiogenesis inhibitors with photodynamic therapy (Ukrainian Journal of Ophthalmology, 2026)
Objective: To compare clinical and structural outcomes of combination therapy (anti-VEGF + PDT) versus anti-VEGF monotherapy in patients with pachychoroid neovasculopathy (PNV) during 12-month follow-up.Materials and Methods: The study included 64 patients (74 eyes) with PNV. Examinations were performed prior to treatment and at designated intervals: 1, 3, 6, and 12 months from the beginning of therapy. Patients were divided into two groups: the main group (40 eyes) and the control group (34 eyes). The main group included 34 patients (40 eyes), with baseline central retinal thickness (CRT) of 410.26 ± 113.48 µm and central choroidal thickness (CCT) of 485.89 ± 102.65 µm. The control group included 30 patients (34 eyes), with CRT of 405.89 ± 102.65 µm and CCT of 483.46 ± 102.54 µm. Patients in the main group received the following combined regimen: one intravitreal injection of 6 mg brolucizumab followed by one session of PDT with chlorin e6–based photosensitizer. Thus, during the entire observation period, patients in this group received one Anti-VEGF injection and one PDT session. PDT and brolucizumab injections were performed according to standard protocols. Subsequent treatment cycles were performed in following regimen: the interval between PDT procedures was at least 3 months, while the average interval between brolucizumab injections was approximately 1.5 months. Patients in the control group received three loading injections of 6 mg brolucizumab at 4-week intervals.Results: In the main group, BCVA increased moderately from 0.28 ± 0.14 at baseline to 0.38 ± 0.23 at the 12-month follow-up, whereas in the control group it remained relatively stable, measuring 0.31 ± 0.26 at month 1 and 0.35 ± 0.24 at month 12. Improvement in functional outcomes was accompanied by anatomical improvements: a reduction in central retinal thickness (CRT) from 410.26±113.48 μm to 262.46±146.40 μm at the 12-month follow-up, confirmed by the resorption of subretinal fluid (SRF) and a decrease in retinal pigment epithelium (RPE) detachments. A significant reduction in central choroidal thickness (CCT) was noted—from 485.89±102.65 μm to 413,21±96,23 μm after 1 month, 413,91±92,25 μm after 3 months, 414,21± 106,23 μm after 6 months, 415,30±108,64 μm by the end of the monitoring period. In the control group, improvement in BCVA was less pronounced (0.31±0.26 before treatment and 0.35±0.24 at 12 months). Changes in morphological parameters occurred early: CRT was reduced by the first month of observation (from 405.89±102.65 μm before therapy to 267,35± 43,65 μm after 1 month, 266,45± 93,65 μm after 3 months, 266,45± 93,65 μm after 6 months, followed by a slight raise up to 268,4±43,5μm by the 12-month mark. Therefore, CCT remained stable throughout the treatment period, maintaining a value comparable to baseline (483.46 ± 102.54 μm). A significant reduction in central retinal thickness and central choroidal thickness, as well as improvement in BCVA, was observed in the combination therapy group over the 6- and 12-month follow-up periods compared to the brolucizumab monotherapy group. These effects were associated with the resorption of subretinal fluid as a result of neovascular membrane occlusion. Conclusion: The inclusion of photodynamic therapy (PDT) with a chlorin e6-based photosensitizer in the treatment regimen for pachychoroid neovasculopathy (PNV) leads to the restoration of anatomical and functional parameters and reduces the recurrence of the disease in patients with PNV.
Keywords: pachychoroid neovasculopathy; age-related macular degeneration; photodynamic therapy; central retinal thickness; central choroidal thickness